(untitled) (Praxis Educativa, 2018)
This is a pedagogical action research, within the framework of digital literacy with young people in the Adult Education, “Educación de Personas Jóvenes y Adultas”, developed and studied an introductory experience of coding, using Scratch for autonomous learning. It was carried out in Instrumental Training, in the subject of Information Technology and Telecommunications (ICT) of the Center for Integrated Education of Youth and Adults (CEIA) Selva Saavedra of Temuco. We worked with students at risk of social exclusion. The strategies and methods used in the classroom were evaluated with the Scratch environment –from a critical approach– and the potential of this educational technology for the promotion of autonomy in learning in students who cross the digital divide.